Effects of Simulated Hands on Pain Responses to Heel Stick in Premature Infants - Thacheephan, Thanatchaporn; Daramas, Tipawan; Patoomwan, Autchareeya (Journal of The Royal Thai Army Nurses, 2023)
This quasi-experimental research with a cross-over design investigated the effects of simulated hands on responses to pain, heart rates and oxygen saturation in premature infants. The study examines behavioral and physiological responses to pain of 30 premature infants admitted in the Neonatal Intensive Care Unit. The subjects were recruited based on specified inclusion criteria and randomly assigned in order of treatment to both experimental and controlled conditions. In the experimental condition, each infant received simulated hands embracing. The videos were recorded throughout the process. The Neonatal Infants Pain Scale (NIPS) was used to assess the pain score. The repeated measures ANOVA was used to analyze. The results showed that the infants who received the simulated hands had the mean pain scores during and after the heel stick of the 1st, 3rd, 5th, 7th, and 10th minutes at 2.50, 1.23, 0.43, 0.17, 0.10, and 0 respectively. Moreover, the mean heart rates after the heel stick were 150.83, 145.07, 141.70, 137.97, 135.87, and 134.37 at the 1st, 3rd, 5th, 7th, and 10th minutes which were less than the infants who received routine nursing care. The mean blood oxygen saturation during and after the heel stick at the 1st, 3rd, and 7th minute was greater than those who receive routine nursing care. Therefore, the simulated hand should be used in nursing practice to alleviate pain from heel stick in preterm infants.